Penerapan Model Problem Based Learning Untuk Meningkatkan Aktivitas Belajar Peserta Didik Materi Teks Puisi Kelas X di SMA PGRI 2 Palembang - N, Noviyanti; Muhajaroh, Siti; H, Hetilaniar (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to determine whether the application of the Problem Based Learning model can increase students' learning activities in class X poetry text material at SMA PGRI 2 Palembang. This type of research is Classroom Action Research (PTK) and uses the Kemmis and Taggart model. This research uses 2 cycles. Each cycle consists of planning, implementation, observation and reflection. The subjects of this research were students in class X.7 of SMA PGRI 2 Palembang for the 2023/2024 academic year. Data collection techniques use observation and tests. Data analysis techniques use qualitative and quantitative data analysis. The results obtained from cycle 1 showed that there were 15 people with a percentage of 40.55% who got a score above the KKM. The results obtained from cycle 1 showed that there were 32 people with a percentage of 86.48% who got a score above the KKM. The difference between cycle 1 and cycle 2 is 45.93. So, it can be concluded that there has been an increase in using the Problem Based Learning model in the learning activities of class X.7 students at SMA PGRI 2 Palembang.